Nacho en casa de su prima - Slegers, Liesbet (Zaragoza : Edelvives, 2002)
Nacho has fun when he spends the night at his cousin's house.
Nacho se divierte cuando pasa la noche en la casa de su prima.
Keywords: Sleepovers -- Juvenile fiction; Pasar la noche -- Novela juvenil